San Fernando gateway - Gutierrez, Theodore Andre R.; De Chavez, Kelvin (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
The Northrail Project is a future commuter rail that connects Manila to New Clark City in Central Luzon and involves reviving the old right of way of the defunct Philippine National railways line. San Fernando Pampanga is marked as one of the stops in the future Northrail line, which has the old San Fernando Train Station sitting in the middle of the proposed site. The project is a station design proposal that incorporates context from its heritage district, and suggests an approach in including the old San Fernando Train Station as part of the new station.
Include appendices
Best Thesis (Architecture) AY 2017-2018, 2nd place
Thesis (Bachelor of Science in Architecture--University of the Philippines Diliman
Keywords: Terminals (Transportation).; Railroad terminals